A Tractable Product Channel Model for Line-of-Sight Scenarios. - Fernández-Plazaola, Unai; Moreno-Pozas, Laureano; López-Martínez, Francisco Javier; París-Ángel, José Francisco; Martos-Naya, Eduardo; Romero-Jerez, Juan Manuel (IEEE, 2020)
We present a general and tractable fading model for line-of-sight (LOS) scenarios, which is based on the product of two independent and non-identically distributed κ-μ shadowed power envelopes. Simple closed-form expressions for the probability density function, cumulative distribution function and moment-generating function are derived, which are as tractable as the corresponding expressions derived from a product of Nakagami-m random variables. This model simplifies the challenging characterization of LOS product channels, as well as combinations of LOS channels with non-LOS ones. We leverage these results to analyze performance measures of interest in the contexts of wireless powered and backscatter communications, where both forward and reverse links are inherently of LOS nature, as well as in device-to-device communications subject to composite fading. In these contexts, the proposed model shows a higher flexibility when fitting field measurements with respect to conventional approaches based on product distributions with deterministic LOS, together with a more complete physical interpretation of the underlying propagation characteristics.
https://journals.ieeeauthorcenter.ieee.org/become-an-ieee-journal-author/publishing-ethics/guidelines-and-policies/post-publication-policies/#submitted
Keywords: Retrodifusión; Telecomunicaciones; Sistemas de comunicaciones inalámbricos; Fading channels; Wireless communication; Nakagami distribution; Rician channels; Channel models; Backscatter communications; κ-μ shadowed fading; Product channel; Wireless powered communications; Composite fading